The modern search for the Holy Grail: is neuroscience a solution? - Naor, Navot; Ben-Ze'ev, Aaron; Okon-Singer, Hadas (Frontiers in Human Neuroscience, 2014)
Neuroscience has become prevalent in recent years; nevertheless, its value in the examination of psychological and philosophical phenomena is still a matter of debate. The examples reviewed here suggest that neuroscientific tools can be significant in the investigation of such complex phenomena. In this article, we argue that it is important to study concepts that do not have a clear characterization and emphasize the role of neuroscience in this quest for knowledge. The data reviewed here suggest that neuroscience may 1) enrich our knowledge; 2) outline the nature of an explanation; and 3) lead to substantial empirical and theoretical discoveries. To that end, we review work on hedonia and eudaimonia in the fields of neuroscience, psychology, and philosophy. These studies demonstrate the importance of neuroscientific tools in the investigation of phenomena that are difficult to define using other methods.